Drug-eluting balloons : dip-coated biodegradable films for sustained drug delivery - Nur Hazwani Abu Samah. (2010)
In recent years, increasing revascularization in patients with in-stent restenosis and late-stage thrombosis as a result of Bare Metal Stents and Drug-Eluting Stents administration have been observed. This has identified the urgency for the development of a novel Drug-Eluting Balloons technology to address these two diagnoses. In order to assess DEB’s potential as a functional drug delivery device, dip-coating was the chosen technique to fabricate the drug-eluting films. Films physical observations and Fluorescein Diacetate (FDA) release studies was performed to analyse the possibility of the dip-coating technique and which PLGA/PEG films, as the most suitable for Paclitaxel drug delivery. Despite some unfavourable film phenomena, dip-coating is a feasible technique for DEB fabrication, given the protocols established in this paper. The FDA release studies demonstrated controlled and homogeneous release along the length of films. Simple dimensional alterations may be done on the films fabricated for an optimum controlled release.